Creative Writing Style Integrated with Flipped Book Maker in Writing English Short Story: An Illustrative Case Study - Harahap, Yunita Mutiara; Rahmawati, Wiki Tedi (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
This research focused and aimed to describe the activities conducted by the students to practice creative writing style integrated with flipped book maker application in writing English short story. Students of English Education Study Program from a private university in Medan was selected purposively as the research participant. There were thirteen students involved as the participants. Illustrative case study which primarily a descriptive study of qualitative approach was designed to conduct this research. Observation was used as the research instrument. The whole activities were observed and noted thoroughly during the classroom interaction and the home assignment. The result of this research showed that the students succeeded to write creatively the English short story. They described and narrated the development of characters, events, and situations in the story. Students also provide and illustrate the story with pictures. As the final result, they converted their short story text into a digital flipped book. By combining digital tools with creative writing style, it can enhance students' engagement, creativity, and overall writing proficiency.